The cortisol response to ACTH in pigs, heritability and influence of corticosteroid-binding globulin. (24th August 2015) - Larzul, C.; Terenina, E.; Foury, A.; Billon, Y.; Louveau, I.; Merlot, E.; Mormede, P.
Abstract : In the search for biological basis of robustness, this study aimed (i) at the determination of the heritability of the cortisol response to ACTH in juvenile pigs, using restricted maximum likelihood methodology applied to a multiple trait animal model, and (ii) at the study of the relationships between basal and stimulated cortisol levels with corticosteroid-binding globulin (CBG), IGF-I and haptoglobin, all important players in glucose metabolism and production traits. At 6 weeks of age, 298 intact male and female piglets from 30 litters (30 dams and 30 boars) were injected with 250 µg ACTH(1–24) (Synacthen). Blood was taken before ACTH injection to measure basal levels of cortisol, glucose, CBG, IGF-I and haptoglobin, and 60 min later to measure stimulated cortisol levels and glucose. Cortisol increased 2.8-fold after ACTH injection, with a high correlation between basal and stimulated levels (phenotypic correlation, r p =0.539; genetic correlation, r g =0.938). Post-ACTH cortisol levels were highly heritable ( h 2 =0.684) and could therefore be used for genetic selection of animals with a more reactive hypothalamic–pituitary–adrenocortical axis. CBG binding capacity correlated with cortisol levels measured in basal conditions in males only. No correlation was found between CBG binding capacity and post-ACTH cortisol levels. Basal IGF-I concentration was positively correlated with BW at birth and weaning, and showed a high correlation with CBG binding capacity with a strong sexual dimorphism, the correlation being much higher in males than in females. Basal haptoglobin concentrations were negatively correlated with CBG binding capacity and IGF-I concentrations. Complex relationships were also found between circulating glucose levels and these different variables that have been shown to be related to glucose resistance in humans. These data are therefore valuable for the genetic selection of animals to explore the consequences on production and robustness traits, but also point at pigs as a relevant model to explore the underlying mechanisms of the metabolic syndrome including the contribution of genetic factors.